Global assessment of pain care quality for musculoskeletal disorders: Insights from the quality of care index (QCI) from 1990 to 2021 - Zhicong Xia; Jiangguang Wang; Xia Wen (PLoS ONE, 2025)
Background Musculoskeletal disorders (MSDs) represent a global primary cause of disability, affecting over 1.69 billion individuals and accounting for over 160 million disability-adjusted life years (DALYs) in 2021. Conventional metrics assess care quality inadequately, necessitating a multidimensional evaluation framework. Thus, this study introduces a novel metric — the Quality of Care Index (QCI) — to comprehensively evaluate the MSD landscape. Objective To develop a novel QCI for MSDs and evaluate global trends, disparities, and drivers from 1990 to 2021. Methods Using Global Burden of Disease (GBD) 2021 data across 204 countries, we constructed a composite QCI integrating four domains: Pain Relief Rate(PRR), Opioid Use Rate(OUR), Need-Independent Coverage(NIC), and Patient Satisfaction(PS). These were standardized into a single index using Principal Component Analysis (PCA). Trends were analyzed via Estimated Annual Percentage Change (EAPC), with disparities assessed by Socio-Demographic Index (SDI) and geography. Results Significant increases in MSDs prevalence (over 12.7% of low back pain; near doubling of osteoarthritis) and DALYs occurred globally, driven by aging populations. Geographic Paradox: Lower- and middle-income countries (LMICs; e.g., Vanuatu, Nicaragua, Central African Republic) achieved higher QCI scores than high-income nations (e.g., Italy, Germany, Japan). QCI improved in LMICs (notably for osteoarthritis/neck pain) but stagnated or even declined in high-income regions. DALYs correlated positively with SDI (R = 0.649–0.863; p < 0.001), with steepest rises in middle- and high-SDI areas for low back pain and osteoarthritis. Conclusion The QCI scores reveal critical relationship between MSDs burden and care quality. High-income regions experience challenges of opioid overuse and stagnant patient satisfaction, while LMICs express gains in access and perceived relief. Implementing context-stratified strategies — de-implementing low-value care in high-SDI areas while scaling evidence-based access in resource-constrained regions — constitutes a critical pathway to equitably alleviate the global MSDs burden.